Transsphenoidal Resection of Pituitary Tumors in the United States, 2009 to 2011: Effects of Hospital Volume on Postoperative Complications - Li, Daphne; Johans, Stephen; Martin, Brendan; Cobb, Adrienne; Kim, Miri; Germanwala, Anand V. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Introduction Higher surgical volumes correlate with superior patient outcomes for various surgical pathologies, including transnasal transsphenoidal (TNTS) pituitary tumor resection. With the introduction of endoscopic approaches, there have been nationwide shifts in technique with relative declines in microsurgery. We examined the volume-outcome relationship (VOR) for TNTS pituitary tumor surgery in an era of increasingly prevalent endoscopic approaches.Methods Patients who underwent TNTS pituitary tumor resection between 2009 and 2011 were retrospectively identified in the State Inpatient Database subset of the Healthcare Cost and Utilization Project. Generalized linear mixed-effect models were used to assess odds of various outcome measures. Institutions were grouped into quartiles by case volume for analysis.Results A total of 6,727 patients underwent TNTS pituitary tumor resection between 2009 and 2011. White or Asian American patients and those with private insurance were more likely to receive care at higher volume centers (HVC). Patients treated at HVC (>60 cases/year) were less likely to have nonroutine discharges (3.9 vs. 1.9%; p = 0.002) and had shorter length of stay (LOS; 4 vs. 2 days; p = 0.001). Overall, care at HVC trended toward lower rates of postoperative complications, for example, a 10-case/year increase correlated with a 10% decrease in the rate of iatrogenic panhypopituitarism (odds ratio [OR] = 0.90, 95% confidence interval [CI]: 0.81–0.99; p = 0.04) and 5% decrease in likelihood of diabetes insipidus (OR = 0.95, 95% CI: 0.90–0.99; p = 0.04) on multivariable analysis.Conclusions Our analysis shows that increased case volume is related to superior perioperative outcomes for TNTS pituitary tumor resections. Despite the recent adoption of newer endoscopic techniques and concerns of technical learning curves, this VOR remains undisturbed.
Keywords: pituitary tumor; transsphenoidal; volume-outcome relationship